Social Representation of Non-Academic Work in Mexico in the Light of Cultural Artefacts - Clement, Ute; Fuentes, Paola García; Gold, Stefan; Hunink, Claudia; Raesfeld, Lydia (International Journal for Research in Vocational Education and Training, 2021)
Context: Technical and Vocational Education and Training (TVET) has attracted increasing interest in recent years due to its potential to address productivity and equity challenges, such as better employment prospects, as outlined in the United Nations Sustainable Development Goals (SDGs). Despite the potential of such programmes, the enrolment rate in vocational training at upper secondary level in Mexico is 38.2%, i.e. below the Organisation for Economic Cooperation and Development (OECD) average of 45.7%. This raises the question of possible reasons for the low enrolment rate. Approach: Based on the assumption that attitudes towards non-academic work are culturally anchored in Mexican society, which also shapes the educational and career aspirations of younger generations, the project named Cultural Practice of Non-academic Work in Mexico (KuPraMex), funded by the German Federal Ministry of Education and Research (BMBF), investigates social representations of non-academic work in Mexico. This is done through the analysis of artefacts such as films, murals, etc., as these are part of the tangible culture of a society. As materialised products of human activities or cultural practices, artefacts can be understood as objectifications of social relations and conditions. Therefore, in this context, it is assumed that through the analysis of cultural artefacts, a deeper understanding of how non-academic work is thought, felt, and valued in Mexican society will emerge. Findings: It has been found that the topic on non-academic work is often associated with informality. Moreover, the representations and narratives in cultural artefacts often show that non-academic work, apart from office work, is physically challenging but cognitively undemanding. In terms of access to a company, social networks seem to have enormous relevance. Hierarchies seem rigid and opportunities for promotion limited. However, narratives with more positive attributions regarding non-academic work can also be identified, which state that young people experience a habitus transformation through work. Conclusion: Nevertheless, non-academic work in Mexico seems to lack prestige, which may affect young people's educational and career aspirations and choices. This could mean that those who can afford it prefer to pursue a career in tertiary education rather than opt for a TVET programme. At the macro level, the mentioned lack of prestige could hamper attempts to offer such programmes.